Effect of dissolution rate and subsequent ion release on cytocompatibility properties of borophosphate glasses - Sharmin, Nusrat; Hasan, Mohammad S.; Islam, Md. Towhidul; Pang, Chengheng; Gu, Fu; Parsons, Andrew J.; Ahmed, Ifty (Walter de Gruyter GmbH, 2019)
Present work explores the relationship between the composition, dissolution rate, ion release and cytocompatibility of a series of borophosphate glasses. While, the base glass was selected to be 40mol%P2O5-16mol%CaO-24mol%MgO-20mol%Na2O, three B2O3 modified glass compositions were formulated by replacing Na2O with 1, 5 and 10 mol% B2O3. Ion release study was conducted using inductively coupled plasma atomic emission spectroscopy (ICP-AES). The thermal scans of the glasses as determined by differential scanning calorimetry (DSC) revealed an increment in the thermal properties with increasing B2O3 content in the glasses. On the other hand, the dissolution rate of the glasses decreased with increasing B2O3 content. To identify the effect of boron ion release on the cytocompatibility properties of the glasses, MG63 cells were cultured on the surface of the glass discs. The in vitro cell culture study suggested that glasses with 5 mol% B2O3 (P40B5) showed better cell proliferation and metabolic activity as compares to the glasses with 10 mol% (P40B10) or with no B2O3 (P40B0). The confocal laser scanning microscopy (CLSM) images of live/dead stained MG63 cells attached to the surface of the glasses also revealed that the number of dead cells attached to P40B5 glasses were significantly lower than both P40B0 and P40B10 glasses.